Exploring the application of dietary antioxidant index for disease risk assessment: a comprehensive review - Pourmontaseri, Hossein; Bazmi, Sina; Sepehrinia, Matin; Mostafavi, Ayda; Arefnezhad, Reza; Homayounfar, Reza; Vahid, Farhad (Frontiers in Nutrition, 2025)
Oxidative stress contributes to the development of cardiometabolic diseases and cancers. Numerous studies have highlighted the adverse effects of high reactive oxygen species (ROS) levels in the progression of chronic noncommunicable diseases and also during infections. On the other hand, antioxidants play a crucial role in preventing oxidative stress or postponing cell damage via the direct scavenging of free radicals or indirectly via the Keap1/Nrf2/ARE pathway, among others. Dietary antioxidants can be obtained from various sources, mainly through a plant-based diet, including fruits and vegetables. The dietary antioxidant index (DAI) has been developed to assess total antioxidant intake from diet. This review delineated the performance of DAI in the risk assessment of different diseases. It is suggested that a high DAI score prevents obesity-related diseases, including diabetes mellitus, hyperuricemia, dyslipidemia, and metabolic (dysfunction)-associated steatotic liver disease (MASLD). Additionally, DAI is negatively associated with Helicobacter pylori and Human papillomavirus infection, thus reducing the risk of gastric and cervical cancer. Also, a high intake of antioxidants prevents the development of osteoporosis, miscarriage, infertility, and mental illnesses. However, further prospective observations and clinical trials are warranted to confirm the application of DAI in preventing diseases that have been studied.